Ramsay-Hunt syndrome in HIV patient - Onuki, Maria Eduarda Oliveira (2022)
Introduction  Ramsay-Hunt syndrome type (SRH) type II is defined by the combination of herpes zoster oticus to acute peripheral facial nerve paralysis, described in 1907 by James Ramsay Hunt. Reactivation of latent varicella-zoster virus in the geniculate ganglion of the facial nerve will cause SRH, resulting in inflammation, edema, and compression of the VII cranial pair. However, nerve involvement, and in turn the development of SRH, manifests in less than 1% of infected patients. It is the second most common cause of atraumatic peripheral facial palsy (PFP) and has an incidence of 5 cases/100,000 people, with no sex predilection. Currently, SRH is classically described as a triad of otalgia, ipsilateral facial paralysis, and vesicles near the ear and ear canal; however, motor, sensory, and autonomic impairment when combined result in diverse neurological damage and may cause different symptoms, its diagnosis is mainly clinical. Goal To report the case of an HIV patient associated with SHR, seen by IIER between May and June/2022. Case Report Male, 49 years old, sought care on 05/20/22 in a hospital with complaints of vertigo and intense headache, associated with nausea and vomiting with onset of symptoms one day ago. His personal history was HIV+, diagnosed in 2013 and under regular treatment. On 5/25/22 resurfaced with the same symptoms of vertigo in conjunction with the appearance of an erythematous and painful vesicle in the right auricular region with edema and flushing of the region in association with PFP symptoms. On 05/30/22 he returned to the clinic with the same symptoms as before, and a magnetic resonance imaging of the temporal bones was done, showing an inflammatory process through the contrast at the bottom of the internal auditory canal suggestive of Bell's Palsy. (To see the complet abstract, please, check out the PDF.)